Populist discourse : recasting populism research - Stavrakakis, Yannis (Routledge, 2024)
"Populist Discourse: Recasting Populism Research offers a refreshingly original discourse theory perspective on populist phenomena. Reading this book will help you learn the historical genealogy of significant populist phenomena from the end of the 19th century onwards and the main conceptual/theoretical accounts established to analyze them. Specifics on how mainstream conceptualizations of populism both in academia and public discourse are discussed in order to map new promising avenues for research beyond. Inspired by the works of Ernesto Laclau and Chantal Mouffe, directions and challenges that open themselves up once conceptual reflexivity, theoretical awareness and historical alertness are established as guiding principles in populism research. Accessible language without sacrificing attention to detail, bibliographical support and a focus on the future orientation of populism research, The Populist Scandal is written for an advanced undergraduate and graduate-level school political theory reader, as well as for their professors. Due to its interdisciplinary character, it will appeal to various politically-informed area studies, and the broad field of ideology and discourse analysis"--